2014
DOI: 10.3389/fnhum.2014.00807
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Virtual Characters to Assess and Train Non-Verbal Communication in High-Functioning Autism

Abstract: High-functioning autism (HFA) is a neurodevelopmental disorder, which is characterized by life-long socio-communicative impairments on the one hand and preserved verbal and general learning and memory abilities on the other. One of the areas where particular difficulties are observable is the understanding of non-verbal communication cues. Thus, investigating the underlying psychological processes and neural mechanisms of non-verbal communication in HFA allows a better understanding of this disorder, and poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 188 publications
(267 reference statements)
1
50
0
6
Order By: Relevance
“…Some people with ASD appear to have little interest in social interaction whereas others may have the interest, but do not know how to relate to others [24,25]. People with ASD are often unable to interpret nonverbal communication, such as body language or facial expressions [2,23,24].…”
Section: Social Mediamentioning
confidence: 98%
See 1 more Smart Citation
“…Some people with ASD appear to have little interest in social interaction whereas others may have the interest, but do not know how to relate to others [24,25]. People with ASD are often unable to interpret nonverbal communication, such as body language or facial expressions [2,23,24].…”
Section: Social Mediamentioning
confidence: 98%
“…Many people with ASD have exceptional abilities in visual, music, and academic skills, and about 40% have average to above average intellectual abilities [22]. Nevertheless, people with ASD may experience difficulties with motor coordination, attention, and physical health issues [23], along with difficulties with social skills and communication [24]. They may also find it difficult to initiate and maintain a conversation [2].…”
Section: Social Mediamentioning
confidence: 99%
“…Tartaro and Cassell [2008] suggested that collaborative narratives with virtual peers may offer a structured setting for using contingent discourse. Georgescu et al [2014] reviewed previous research done with virtual characters and virtual reality environments (VRE). They concluded that these provide great value for experimental paradigms in social cognition, specifically those related with non-verbal behavior and perception in participants with high-functioning autism, because it allows to grasp the full extent of the social world in a controlled manner.…”
Section: Virtual Charactersmentioning
confidence: 99%
“…A prototype Internet-based VR apps was Second Life (http:// secondlife.com/) [114]. Virtual characters and environments represent a valuable tool for the supportive therapies and the training of social skills and non-verbal decoding (e.g., high-functioning autism), as they provide a safe, repeatable and diversifiable learning environment [115]. There are few problems, though as when participating in violent games, avatars personalize risk by simulating harm to digital representations with which people directly identify, and this may be upsetting [116] Another type of a VR platform is a fully immersive system.…”
Section: Innovations or Additions To Regular Traditional Treatmentsmentioning
confidence: 99%